Room‐Temperature Carbon Nanotube Single‐Electron Transistors with Mechanical Buckling–Defined Quantum Dots. (14th April 2018) - Zhang, Jian; Liu, Siyu; Kong, Lingyuan; Nshimiyimana, Jean Pierre; Hu, Xiao; Chi, Xiannian; Wu, Pei; Liu, Jia; Chu, Weiguo; Sun, Lianfeng
Abstract: Single‐electron transistors (SETs) have been proposed as a future alternative to conventional Si‐based electronics. However, their practical applications are strongly limited because most SETs operate at cryogenic temperatures. In this work, room temperature operating SETs are successfully fabricated with the realization of a mechanical buckling–defined quantum dot within a suspended and strained single‐walled carbon nanotube. Clear Coulomb oscillations are observed at room temperature due to the Coulomb blockade effect. The Coulomb charging energy is calculated to be 160 meV, which substantially exceeds the thermal energy. At 10 K, the Coulomb staircases are observed in the current–voltage characteristics with an energy level separation ≈29 meV, confirming that the island behaves as a well‐defined quantum dot for the electrons. This device fabrication method may also help future investigations into the electromechanical properties of nanotube quantum systems. Abstract : Room temperature operating single‐electron transistors are successfully fabricated with the realization of a mechanical buckling–defined quantum dot within a suspended and strained single‐walled carbon nanotube. Clear Coulomb oscillations are observed at room temperature, which is due to the Coulomb blockade effect. The Coulomb charging energy is calculated to be 160 meV, which substantially exceeds the thermal energy.